ЕДИГЕ-ҚАРАҚАЛПАҚ ХАЛҚЫНЫҢ МИЛЛИЙ ҚАҲАРМАНЫ, ЯМАСА ДӘСТАН ҚАҲАРМАНЫ ЕДИГЕНИҢ ЭТНИКАЛЫҚ КЕЛИП ШЫҒЫЎЫНА БАЙЛАНЫСЛЫ МОТИВЛЕРДИҢ ТАРИЙХЫЙ-ФОЛЬКЛОРЛЫҚ ТИПОЛОГИЯСЫ - Алламбергенов, К. (ILIM hám JÁMIYET, 2019)
The article is devoted to one of the actual issues in the study of eposes-the investigation of off-springs, ethnic origin, tribe and clan, ethnos, nation of the leading hero of the epos «Edige»-Edige on the basis of the comparative analysis of historical-folklore materials. The authors of the article tries to prove and confirm the opinion that Edige belonged to the clan Mangit, its branch –Ak Mangit.